Genetic inheritance pattern in prurigo Hebra - Siti Aisah Boediardja; Wahyuning Ramelan; Santoso Cornain (Paediatrica Indonesiana, 2001)
A study was conducted to analyze the multifactorial genetic inheritance pattern in prurigo Hebra (PH). Fiftyprobands (PH patients) consisting of 11 males and 39 females, with age ranged from 5-30 years were included in this study.A three-generation family tree was obtained from each subject, from which a total of 79 families were eligible for analysis. Foreach family the possible mode of inheritance, namely autosomal dominant (AD) or autosomal recessive (AR), was predicted.The families were then grouped according to the mode of inheritance. Analysis was conducted using Chi-square test,comparing the observed occurrence of PH and the expected value for each mode. To rule out mutation, the second methodwas applied, which only families with more than one affected child were analyzed, was used. The genetic inheritancepattern was not consistently compatible either with AR or AD. This finding, and other supporting facts, such as femalepreponderace, the role of HLA and the lower morbidity rate compared to the expected rate in AR or AD mode, indicated thatthe genetic inheritance of PH follows a multi-factorial pattern.